Between Una serata in famiglia and Ekìdrosi. About Giorgio Manganelli's Sconclusione - Luigi Weber (Finzioni, 2021)
The essay focuses on one of Giorgio Manganelli's least studied works, Sconclusione, published in 1976 and never reprinted. It analyses the peculiar, apparently non-Manganellian, style of the novel, humble, almost banal, and interprets it in the light of the contrast between it and the author's back cover, which is instead markedly in tune with the author's voice. In order to do this, the critical notion of pastiche is used, misaligning it from the usual value given to it in the Italian cultural panorama (mixture of styles) as well as from the international one (imitation), in order to propose an idea of autopastiche, intended as an (intentionally) imperfect imitation of one's own style by an author.